2009
DOI: 10.2527/jas.2008-1563
|View full text |Cite
|
Sign up to set email alerts
|

Effect of zilpaterol hydrochloride duration of feeding on performance and carcass characteristics of feedlot cattle1

Abstract: Four trials, each with a randomized complete block design, were conducted with 8,647 beef steers (initial BW = 346 +/- 29.6 kg) in 3 different locations in the United States to evaluate the effects of zilpaterol hydrochloride (ZH) on performance and carcass characteristics of feedlot cattle. Treatments consisted of feeding ZH (8.33 mg/kg of dietary DM) for 0, 20, 30, or 40 d, at the end of the feeding period, followed by a 3-d withdrawal period before slaughter. Cattle were weighed on d 0 and 50 before slaught… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
56
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 5 publications
18
56
4
Order By: Relevance
“…34,40 Elam et al treated Bos taurus bulls with 8.33 mg ZH/kg feed as dry matter for 30 days and obtained final weight increments of 9.3 kg compared with untreated bulls. 42 These values are similar to those obtained in this trial for Bos indicus (i.e., final weight increments of 7.75 kg at a dose of 6 mg of generic ZH/kg feed). The mean final weight reported by Avendaño et al using a generic ZH, was higher than the one achieved here 21 ; however, the weight gain reported by these authors was similar to the corresponding value obtained during this trial (e.g., 77.80 vs. 53.16, respectively).…”
Section: Generic Zilpaterol Hcl In Bos Indicussupporting
confidence: 85%
See 1 more Smart Citation
“…34,40 Elam et al treated Bos taurus bulls with 8.33 mg ZH/kg feed as dry matter for 30 days and obtained final weight increments of 9.3 kg compared with untreated bulls. 42 These values are similar to those obtained in this trial for Bos indicus (i.e., final weight increments of 7.75 kg at a dose of 6 mg of generic ZH/kg feed). The mean final weight reported by Avendaño et al using a generic ZH, was higher than the one achieved here 21 ; however, the weight gain reported by these authors was similar to the corresponding value obtained during this trial (e.g., 77.80 vs. 53.16, respectively).…”
Section: Generic Zilpaterol Hcl In Bos Indicussupporting
confidence: 85%
“…Most trials using the reference ZH brand were conducted in temperate/cold areas, which have predominant Bos taurus bulls 33,[42][43][44] . After a thorough literature review, only two trials could be compared with the one described here.…”
Section: Generic Zilpaterol Hcl In Bos Indicusmentioning
confidence: 99%
“…Calf-fed Holstein steers fed ZH had an increased (P < 0.01) percentage of USDA Select grading carcass (31.0) and a decreased (P < 0.01) percentage of USDA Choice grading carcasses (65.0) compared with steers fed RH (25.8,70.2) or the control diet (24.8, 72.0), respectively. The results from the current study with respect to QG are generally consistent with those of Beckett et al (2009) and Elam et al (2009), who collectively reported feeding ZH increased the percentage of USDA Select grading carcasses (11.7% to 12.3%) and decreased the percentage of USDA Choice grading carcasses (5.8% to 12.0%) over cattle fed no β-agonist. No differences (P ≥ 0.49) were observed between treatments for the percentage of USDA Standard or Prime grading carcasses.…”
Section: Carcass Characteristicssupporting
confidence: 78%
“…Skeletal, lean, overall maturity, color, and dark cutter scores were not affected by feeding ZH. Steer studies have demonstrated no difference in lean maturity when fed ZH 0, 20, 30, or 40 d or when the cattle had differ ent days on feed (Vasconcelos et al, 2008;Elam et al, 2009). Hilton et al (2009) found LM steaks from cattle fed ZH 30 d, vacuum-aged 14 d postmortem, and pack aged with polyvinyl chloride (PVC) film for retail dis play maintained a brighter cherry red color throughout the 5-d retail display than did the controls.…”
Section: %) Feeding Zh Tended Tomentioning
confidence: 99%
“…Interestingly, even though BW is increased an aver age of 9 kg in beef steers fed ZH compared with control steers, HCW was increased approximately 15 kg (Vas concelos et al, 2008;Elam et al, 2009). The increase in HCW relative to BW resulted in changes in dressing percent.…”
Section: Feedlot Performancementioning
confidence: 99%